The most valued characteristic of clinical instructors perceived by nursing students - Yulia Martiningsih Karmila Letor (NHM PRESS, 2021)
Clinical teaching effectiveness has been a topic of interest in nursing education over the last few decades. An effective clinical teaching guided by clinical instructors intends to create high, updated core clinical competencies and link them with theoretical knowledge of nursing students. Clinical instructors, thus, are seen as one of the key parts in nursing education. This study aimed to expand the most recent integrative literature review on the topic of the most valued characteristic of clinical instructors perceived by nursing students which was conducted by Angela Dawn Collier in 2017. Similar with hers, an integrative literature review was also employed in this study. 13 related literature published from 2018 up to February 2021 were integrated reviewed and synthesized. It was found that personality trait was the most valued characteristic of nursing clinical instructors. This finding also means that knowing their instructor have good personality was the highest expectation of the students. A scientific implication of this finding is that more studies are always needed to reconceptualize or expand this topic. Practically, well-defined expectations of nursing students in clinical settings should always be explored.